Influência do período climático sobre os constituintes bioquímicos do plasma seminal de catetos (pecari tajacu linnaeus, 1758) criados em região semiárida - Moreira, Samara Sandy Jerônimo (Universidade Federal Rural do Semi-Árido, 2019)
The Collared peccary is a Tayassuid abundant in the South American fauna, of great ecological and economic potential. In order to extend the knowledge about its reproductive biology, we studied the influence of climatic periods in a semiarid climate on its seminal parameters and biochemical profile of seminal plasma. For this, the ejaculate of 12 adult males was obtained by electroejaculation during the dry period (September to November 2017) and rainy (February to April 2018) and then analyzed for volume, concentration, motility, membrane functionality, integrity of the membrane, condensation status of chromatin, sperm morphology and pH. For biochemical analysis, the samples were centrifuged at 385 × g for 10 minutes and the supernatant stored at -20 ° C until analysis, where they were heated at 25 ° C for 2 minutes and analyzed by commercial biochemical kits, whose absorbances were measured in a spectrophotometer using the suggested wavelengths of each kit. The results were expressed as mean and standard error and compared by ANOVA followed by the Tukey test (P <0.05). The sperm and biochemical parameters were correlated to each other through the Spearman correlation (p <0.05). During the dry period, the ejaculates presented volume of 1.85 ± 0.4 mL, concentration of 245.8 ± 50.2 spermatozoa / mL, 64.3 ± 6.4% of mobile spermatozoa, 75.3 ± 5, 5% spermatozoa with functional membrane, 84.9 ± 2.3% spermatozoa with whole membrane, 99.6 ± 0.1% spermatozoa with condensed chromatin, 80.4 ± 4% morphologically normal spermatozoa and pH 7.9 ± 0.3a. In the rainy season, the values obtained were 1.87 ± 0.5 mL for volume, 295.8 ± 60.6 sperm / mL, 58.5 ± 9.1% for spermatozoa, 80.3 ± 2.9 % of spermatozoa with functional membrane, 81.8 ± 1.3% spermatozoa with intact membrane, 99.1 ± 0.3% spermatozoa with condensed chromatin, 72.1 ± 7.1% normal spermatozoa and pH 8.5 ± 0.3b. Concerning the biochemical profile, no differences (P> 0.05) were found between the stations for several constituents of the seminal plasma, with values of 140.8 ± 36.03 mg / dL and 169.7 ± 19.9 mg / dL for citric acid, 152.3 ± 33.65 mg / dL and 332.0 ± 99.6 mg / dL for cholesterol, 8.0 ± 2.26 g / dL and 7.0 ± 1.5 g / dL for total proteins, 5.7 ± 0.5 mg / dL and 5.9 ± 0.24 mg / dL for magnesium, 315.6 ± 103.94 mEq / L and 271.3 ± 45.57 mEq / L for chlorides , 9.4 ± 3.26 g / dL and 3.0 ± 0.64 g / dL for albumin and 12.3 ± 5.0 mg / dL and 75.1 ± 39.53 mg / dL for phosphorus, 210 , 9 ± 93.9 μg / dL and 423.2 ± 228.1 μg / dL for iron and 403.6 ± 117.6 mmol / L and 198.4 ± 108.0 mmol / L for fruits, obtained during dry and rainy seasons, respectively. On the other hand, fructose (115.7 ± 44.2a mg / dL / 849.2 ± 142.6b mg / dL) and calcium (15.6 ± 5.09a mg / dL / 32.3 ± 5.3b mg / dL) were significantly more prevalent in the rainy season (P <0.05). In conclusion, the periods (dry and rainy) in semiarid climate exert an effect on the seminal quality and some biochemical constituents (fructose and calcium) of the seminal plasma, in addition, these biochemical components exert action on the sperm quality of Collared peccary
Keywords: Bioquímica; plasma seminal; semiárido; Biochemistry; seminal plasma; semiarid; CIENCIAS AGRARIAS::MEDICINA VETERINARIA